COTAS RACIAIS NA UNIVERSIDADE PÚBLICA BRASILEIRA: com a palavra, o cotista negro - Pinheiro, Marielli Ramos (2014)
There has been a transformation in the Brazilian public university with the intention to democratize access to higher education: the racial quotas for blacks. The purpose of this affirmative action is to create opportunities in order to increase access to education for blacks. Although this policy has been adopted by some universities for a long time, just in 2012 the Law number 12.711 was enacted. This Act provides for the admission of black students at Federal Universities and Federal Institutions of mid-level technical education. The main objective of the present study is to understand how the policy of racial quotas for blacks at Universidade Estadual de Ponta Grossa - UEPG - Paraná, produces relations/tensions in the construction of ethnic identity of undergraduates. The specific objectives are: i) to identify which experiences of UEPG students were fundamental to the formation of their ethnic identity; ii) to know how undergraduates perceive themselves as quota holders and blacks before a controversial scenario concerning racial quotas and racism in Brazil; iii) and understand how UEPG identifies/evaluates candidates as black/African descents. For the purpose of this study, we conducted a literature review about the issue by consulting the Laws that govern this affirmative policy, by analyzing the UEPG documents that are related to the adoption of the quota policy, by looking at evaluation reports on the implementation of quotas for blacks, and by searching scientific research which deal with issues related to the black race and its correlates. Furthermore, it was possible to attend the Committee for Evaluating the Condition of Black Candidate, on the Summer Vestibular 2013, in order to observe and analyze the criteria under which such candidates are evaluated to become eligible or not for the quotas. As part of the research, we used an interview to learn about the experiences of black quota of UEPG students. Ten students who were willing to contribute to our study told their history of life, what influenced their choice to bid for shares in the vestibular and reported their perceptions about the quota policy in UEPG, among other issues. We concluded, based on the analysis, that the sense of belonging to a black ethnicity is related to color and phenotypic characteristics, which was perceived in both groups under analysis: the students and the university in the figure of the Committee. This leads to an interpretation of a lack of politicization in the arguments brought by students to explain what being black and being a quota holder in UEPG means. The results point to the need to accommodate the demands that affirmative actions, in general, bring with them, such as the discussion of racial prejudice, the difficulty of keeping up with higher education, the need to balance work and study due to spending on housing, food, and transportation. Therefore, we believe it is important to address this issue collectively within the internal and external environment of the academic community.